2019
DOI: 10.1089/chi.2018.0247
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Risk of Obesity by Sex: Nine-Year Follow-Up of the Young Lives Study in Peru

Abstract: Background: We aimed to evaluate if there is association between hours of sleep and the risk of obesity among children and whether this association differs by sex. Methods: A secondary data analysis, using information of the Young Lives study, was conducted. The outcome was obesity, based on the BMI for age z-score; the exposure was child's sleep duration (reported by parents) categorized using the National Sleep Foundation guidelines, and as a numerical variable. Baseline and three follow-ups information were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The association between sleep duration, sleep quality, and overweight/obesity was analyzed (Table 3 ). The group of samples with long sleep duration was not included in regression model because of small sample size ( n = 14) and low prevalence of long sleep duration (0.69%) and thus could not provide sufficient statistical power [ 47 , 48 ]. Univariate associations between sleep duration, sleep quality, and overweight/obesity of all participants were initially analyzed in Model 1.…”
Section: Resultsmentioning
confidence: 99%
“…The association between sleep duration, sleep quality, and overweight/obesity was analyzed (Table 3 ). The group of samples with long sleep duration was not included in regression model because of small sample size ( n = 14) and low prevalence of long sleep duration (0.69%) and thus could not provide sufficient statistical power [ 47 , 48 ]. Univariate associations between sleep duration, sleep quality, and overweight/obesity of all participants were initially analyzed in Model 1.…”
Section: Resultsmentioning
confidence: 99%
“…53,54 Obesity development is multifactorial. 55 That said, many pediatric studies (though not all 56 ) report a correlation between insufficient sleep and the odds of current obesity 24,25,57,58 as well as prospective risk of weight gain. 59,60 In pediatric studies that utilized actigraphy to objectively measure sleep duration, there is evidence of associations between short sleep duration and risk of general 35,61,62 and/or central obesity risk.…”
Section: Sleep Duration and Obesitymentioning
confidence: 99%
“…Finally, as noted previously, there is evidence of an association between long sleep duration and increased risk of obesity. 56 This association is likely multifactorial, and may be impacted by confounders such as depressive symptoms, sleep fragmentation, photoperiodic abnormalities, chronic fatigue, and/or an underlying disease process such as obstructive sleep apnea (OSA) or cardiovascular disease. 80…”
Section: Obesitymentioning
confidence: 99%
“…Obesity is a serious global public health problem and is considered a pandemic. It is the second most common preventable cause of death after smoking[ 1 - 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of the World Health Organization, it is predicted that in 2030, approximately 60% of the world’s population will be affected by and 1.1 billion people will be obese[ 6 ]. It has been reported that the prevalence of obesity in Turkey has increased in parallel with that in other European countries and has reached high rates of 37% of overweight individuals and 36% of obese individuals[ 1 ]. Obesity causes more than 700 billion dollars of health expenditure globally every year.…”
Section: Introductionmentioning
confidence: 99%